Characterization of two P-450 isozymes placed in the rat CYP2D subfamily - Ohishi, Norihisa; Imaoka, Susumu; Suzuki, Tokuji; Funae, Yoshihiko (Biochimica et biophysica acta, 1993)
Two P-450s with debrisoquine 4-hydroxylation activity, designated P-450 UT-7 and UT-7b, were purified and partially purified, respectively, from hepatic microsomes of untreated male rats. Both purified P-450s with an apparent molecular weight of 49 000, were associated with another protein with an apparent molecular weight of 29 000 which was designated 29 k-protein. The CO-reduced spectra of both P-450 UT-7 and UT-7b showed a peak at 448 nm. The NH2-terminal amino acid sequences of P-450 UT-7 and UT-7b were the same as the amino acid sequences of CYP2D1 and CYP2D2 deduced from the cDNA, respectively, except for the lack of a terminal methionine for P-450 UT-7b. In a reconstituted systems, P-450 UT-7 and UT-7b catalyzed lidocaine 3-hydroxylation and N-deethylation in the presence of the 29 k-protein. The Km and Vmax values for lidocaine 3-hydroxylation were 3.6 μM and 0.50 nmol/min/nmol of P-450 for P-450 UT-7, and 3.6 μM and 0.93 nmol/min/ nmol of P-450 for P-450 UT-7b, respectively. Antibody against P-450 UT-7, which also cross-reacted with P-450 UT-7b, inhibited lidocaine 3-hydroxylation in liver microsomes from untreated male rats, but had little effect on lidocaine N-deethylation. These findings suggested that lidocaine 3-hydroxylation in hepatic microsomes from untreated male rats was catalyzed by P-450 UT-7 and/or UT-7b. P-450 UT-7 not containing 29 k-protein was obtained as the non-absorbed fraction from hydroxylapatite HPLC. The activities of debrisoquine 4-hydroxylation as well as lidocaine 3-hydroxylation and N-deethylation in a reconstituted system with P-450 UT-7 without 29 k-protein were one-fifth of those of P-450 UT-7 containing 29 k-protein at the same substrate concentration. These findings suggested that the 29 k-protein was essential to express the maximal metabolic activities. However, the lidocaine metabolic activity in a reconstituted system with P-450 UT-7 containing 29 k-protein and in hepatic microsomes were not inhibited by 29 k-protein antibody.